Effects of soybean meal replacement with fermented soybean meal on growth, serum biochemistry and morphological condition of liver and distal intestine of Florida pompano Trachinotus carolinus. (30th October 2017) - Novriadi, R.; Rhodes, M.; Powell, M.; Hanson, T.; Davis, D.A.
Abstract: This study evaluated the suitability of commercially produced fermented soybean meal (FSBM) known as PepSoyGen™, in a plant‐based diet for Florida pompano, Trachinotus carolinus fingerlings. An 8‐week growth trial was conducted to evaluate the effect of four isonitrogenous and isolipidic diets containing 0, 206, 309 and 410 g/kg FSBM, replacing approximately 0%, 50%, 75% and 100% SBM (designated as Basal, FSBM 50, FSBM 75 and FSBM 100, respectively) on growth performance, body composition, serum biochemistry and morphological condition of liver and distal intestine of Florida pompano. There were no significant differences in final mean weight, percentage weight gain, thermal unit growth coefficient and feed conversion ratio in all treatments. For serum biochemistry analysis, there were no significant differences in total protein, albumin, glucose, cholesterol, bile acids, plasma alkaline phosphatase, alanine aminotransferase and aspartate aminotransferase activities in all treatments. Cellular infiltration, presence of goblet cells and the width of lamina propria in the distal intestine were partly improved in fish fed FSBM 75 and 100 compared to the fish fed FSBM 50 and basal diet. Glycogen granulation, inflammation and nuclear change condition in the liver of pompano were better as the inclusion of fermented product increased. Results of this study indicate that FSBM can be utilized as an alternative protein source and microbial fermentation process could improve the functional properties of SBM.